2020
DOI: 10.4103/ijmr.ijmr_1896_20
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory surveillance for SARS-CoV-2 in India: Performance of testing & descriptive epidemiology of detected COVID-19, January 22 - April 30, 2020

Abstract: Background & objectives: India has been reporting the cases of coronavirus disease 2019 (COVID-19) since January 30, 2020. The Indian Council of Medical Research (ICMR) formulated and established laboratory surveillance for COVID-19. In this study, an analysis of the surveillance data was done to describe the testing performance and descriptive epidemiology of COVID-19 cases by time, place and person. Methods: The data were extracted from January 22 to April 30, 2020. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 8 publications
4
38
1
Order By: Relevance
“…11,17,19,20,22,25 The majority of the cases in this study were in the working-age group (19-49 years) which was also similar to the previously reported studies. 11,22,25 This study reports a low mean room per person data. As per international standards, the data quoted by the "Organization for Economic Co-operation and Development (OECD)", the average home contains 1.8 rooms per person.…”
Section: Discussionsupporting
confidence: 91%
“…11,17,19,20,22,25 The majority of the cases in this study were in the working-age group (19-49 years) which was also similar to the previously reported studies. 11,22,25 This study reports a low mean room per person data. As per international standards, the data quoted by the "Organization for Economic Co-operation and Development (OECD)", the average home contains 1.8 rooms per person.…”
Section: Discussionsupporting
confidence: 91%
“…It is plausible that these latter were also contacts of SARS-CoV-2 carriers. The age and sex profile of our study set matches nationwide surveillance data from India, reported by Abraham et al, with median age and age-distribution close to our sample, and a similar high attack rate in males [17].…”
Section: Discussionsupporting
confidence: 89%
“…Deaths, however, occurred overwhelmingly among elderly patients. The age and sex profile of our study set matches nationwide surveillance data from India, with median age and age-distribution close to our sample, and a similar high attack rate in males [17].…”
Section: Discussionsupporting
confidence: 79%
“…Field workers, trained to elicit travel and contact history, carried out telephonic and house-to-house surveys to identify primary and secondary contacts of positive cases. On average, 47.4 contacts were tested for each confirmed case [17]. Data collected at the community level was collated by the State War Room.…”
Section: Data Sourcementioning
confidence: 99%